THE PSYCHOLOGICAL AND SOCIAL IMPACTS OF WORKER-MACHINE INTERACTIONS IN THE MANUFACTURING INDUSTRY: A SYSTEMATIC LITERATURE REVIEW - Timotius, Elkana (J@ti Undip: Jurnal Teknik Industri, 2023)
Accidents and occupational diseases occur frequently, especially in the manufacturing industry. Workers also have psychological burdens in the industrial era 4.0 as indicated by the increase in cases of stress experienced when interacting with machines. These concerns led this study to reduce the psychological and social negative impacts on workers interacting with machines. This was achieved through a systematic literature review using the PRISMA stages to comprehensively determine the burden experienced by workers and their impact. It was discovered from the 14 articles that meet the search criteria that the psychological and social conditions of workers are very bad mainly due to the application of technology in the Industry 4.0 era. This was caused by eight factors which include (1) workload exceeding capacity, (2) high concentration and cognitive activity demanded at work, (3) increased cognitive load, (4) anxiety about their ability to use technology, (5) work becoming increasingly complex, (6) worried that their position will be replaced by technology, (7) inability to operate technology, and (8) reduced social interaction. It was recommended that the impact be reduced by managing the causative burdens using two main approaches which include the company and the individual worker affected.